Synthesis of novel inhibitors blocking Wnt signaling downstream of β‐Catenin. Issue 5 (25th January 2013) - Halbedl, Sonja; Kratzer, Marie-Claire; Rahm, Karolin; Crosta, Nicoletta; Masters, Kye-Simeon; Zippert, Jessica; Bräse, Stefan; Gradl, Dietmar
Abstract : Large scale screening of libraries consisting of natural and small molecules led to the identification of many small molecule inhibitors repressing Wnt/β‐Catenin signaling. However, targeted synthesis of novel Wnt pathway inhibitors has been rarely described. We developed a modular and expedient way to create the aromatic ring system with an aliphatic ring in between. Our synthesis opens up the possibility, in principle, to substitute all positions at the ring system with any desired substituent. Here, we tested five different haloquinone analogs carrying methoxy‐ and hydroxy‐groups at different positions. Bona fide Wnt activity assays in cell culture and in Xenopus embryos revealed that two of these compounds act as potent inhibitors of aberrant activated Wnt/β‐Catenin signaling. Abstract : ► We developed an easy method to synthesize novel Wnt inhibitors based on the structure of haloquinone. ► This allows to design novel inhibitors simply by modifying the functional groups at the backbone. ► Two compounds inhibit Wnt/β‐Catenin signaling in two independent bona fide Wnt‐activity assays. ► The new inhibitors block endogenous Wnt‐driven transcription. ► Symmetrical compounds act as Wnt antagonists, asymmetrical compounds do not.